Changes in drug use behaviors coinciding with the emergence of illicit fentanyl among people who use drugs in Vancouver, Canada. (2nd September 2020) - Brar, R; Grant, C; DeBeck, K; Milloy, M-J; Fairbairn, N; Wood, E; Kerr, T; Hayashi, Kanna
ABSTRACT: Background : With the emergence of illicitly-manufactured fentanyl, drug overdose deaths have risen in unprecedented numbers. In this context, there is an urgent need to characterize potential changes in drug use behaviors among people who use drugs (PWUD). Objective : To examine changes in drug use behaviors following the emergence of illicit fentanyl among people who use drugs (PWUD). Methods : Data for this cross-sectional analysis was derived from three prospective cohorts of PWUD between December 2016 and May 2017 in Vancouver, Canada. Multivariable logistic regression was used to determine factors associated with self-reported behavior changes (binary variable "yes" or "no") following the emergence of illicit fentanyl. Results : Among 999 participants [363 (36.3%) females], 388 (38.8%) reported some behavior change. The remaining 611 (61.2%) reported no change in behavior; 240 (39.3%) of these individuals had recently been exposed to fentanyl. In multivariable analyses, factors independently associated with behavior change included recent non-fatal overdose (Adjusted Odds Ratio [AOR] = 2.28), active injection drug use (AOR = 1.96), being on opioid agonist therapy (AOR = 1.80), and urine drug screen positive for fentanyl (AOR = 1.45), (all p < .05). Conclusion : The majority of PWUD in our sample did not change their drug use behavior despite a high prevalence of fentanyl exposure, indicating a need for targeted behavior change messaging and overdose prevention efforts such as naloxone and addiction treatment for this sub-population of PWUD. Further, the high fentanyl exposure observed in our sample suggests a need to address upstream structural factors shaping the overdose risk in addition to individual behavioral change.